Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00428-008-0717-3
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological predictor for regional lymph node metastasis in gastric cancer

Abstract: Regional lymph node metastasis in gastric cancer is a definitive indicator of the patient's prognosis. The goal of this study was to identify the predictors for lymph node metastasis among all the possible histopathological parameters, especially by conducting an objective discrimination of the lymphatic and blood vessels. A total of 210 resected primary gastric cancers with or without lymph node metastasis were evaluated based on the conventional histopathological parameters together with immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
(47 reference statements)
3
5
0
Order By: Relevance
“…The lymphatic system is known to be scarcer than the blood network on the gastric wall [20]. This difference was consistent with the results of two other studies regarding the MVD obtained by markers of the lymphatic and blood endothelium in CG [13,18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lymphatic system is known to be scarcer than the blood network on the gastric wall [20]. This difference was consistent with the results of two other studies regarding the MVD obtained by markers of the lymphatic and blood endothelium in CG [13,18].…”
Section: Discussionsupporting
confidence: 91%
“…Some authors do not even register the precise definition of the microscopic field area used for counting. Previous series of GC using CD34 found MVD values much lower as compared to our study, but those values were expressed only by number of microvessels per field of 200x or 400x, but not by mm 2 [11,14,18]. Only two other studies show similar values to our MVD results [13,19].…”
Section: Discussionsupporting
confidence: 65%
“…Arigami et al 54 showed a correlation between VEGF-C and -D over-expression in primary tumor obtained by RT-PCR and the presence of lymph node micrometastasis in early gastric cancer. These results were confirmed by Morita et al 55 that found a relation between VEGF-C expression and lymph nodes metastases only in early gastric cancer. Kondo et al 56 demonstrated a correlation between positive immnunoreactivity of both VEGF-C and -A and lymph node metastasis in gastric cancer.…”
Section: Vascular Endothelial Growth Factor (Vegf)supporting
confidence: 78%
“…Vascular endothelial growth factor C (VEGF-C) and its receptor, VEGF receptor 3 (VEGFR-3), have been identified as the principal growth factors and the vital receptor for lymphangiogenesis in a variety of human malignancies, including gastric cancer [14]. However, the signaling pathway activated by the interaction between VEGF-C and VEGFR-3 in tumor cells is still unknown.…”
Section: Introductionmentioning
confidence: 99%